2003
DOI: 10.1093/comjnl/46.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Transient Analysis of Rewarded Continuous Time Markov Models by Regenerative Randomization with Laplace Transform Inversion

Abstract: In this paper we develop a variant, regenerative randomization with Laplace transform inversion, of a previously proposed method (the regenerative randomization method) for the transient analysis of rewarded continuous time Markov models. Those models find applications in dependability and performability analysis of computer and telecommunication systems. The variant differs from regenerative randomization in that the truncated transformed model obtained in that method is solved using a Laplace transform inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The first one is taken from (Carrasco, 2003b) and corresponds to a RAID 5 storage system (Chen et al, 1994) with the architecture shown in Figure 1. The system comprises 40 × 5 disks, 5 controllers, 3 hot spare disks, and 1 hot spare controller.…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one is taken from (Carrasco, 2003b) and corresponds to a RAID 5 storage system (Chen et al, 1994) with the architecture shown in Figure 1. The system comprises 40 × 5 disks, 5 controllers, 3 hot spare disks, and 1 hot spare controller.…”
Section: Examplesmentioning
confidence: 99%
“…The initial probability is one for the fully operational state and is zero for the remaining states. As in (Carrasco, 2003b), we assume that if unavailable disks do not belong to the same string, when one of them becomes available the remaining unavailable disks still belong to different strings whenever their number is ≥ 2. The CTMC has 14 081 states and 94 405 transition rates.…”
Section: Examplesmentioning
confidence: 99%